Selling and Smooth-Talking: Effects of Interviewer Impression Management from a Signaling Perspective - Wilhelmy, Annika; Kleinmann, Martin; Melchers, Klaus G.; Götz, Martin (Frontiers in Psychology, 2017)
Prior research suggests that interviewers play an important role in representing their organization and in making the interview a pleasant experience for applicants. This study examined whether impression management used by interviewers (organization-enhancement and applicant-enhancement) is perceived by applicants, and how it influences applicants’ attitudes, intentions, and emotions. Adopting a signaling perspective, this article argues that applicants’ positive attitudes and intentions towards the organization increase if interviewers not only enhance the organization, but if the signals they sent (i.e., organization-enhancement) are actually received by the applicant. Similarly, applicants’ positive emotions should increase if interviewers not only enhance the applicant, but if the signals they send (i.e., applicant-enhancement) are actually received by the applicant. A field study which involved video coding interviewers’ impression management behavior during 153 selection interviews and pre- and post-interview applicant surveys showed that the signals sent by interviewers during the interview were received by applicants. In addition, applicants rated the organization’s prestige and their own positive affect after the interview more positively when they perceived higher levels of organization-enhancement during the interview. Furthermore, applicants reported more positive affect and interview self-efficacy after the interview when they perceived higher levels of interviewer applicant-enhancement. We also found an indirect effect of interviewers’ organization-enhancement on organizational prestige through applicants’ perceptions of organization-enhancement as well as indirect effects of interviewers’ applicant-enhancement on applicants’ positive affect and interview self-efficacy through applicants’ perceptions of applicant-enhancement. Our findings contribute to an integrated understanding of the effects of interviewer impression management and point out both risks and chances in selling and smooth-talking towards applicants.